Penggusuran Sebagai Wujud Dari Konflik Agraris Di Desa Sena - Ani, Desi Putri; Marsa, Yummy Jumiati (Jayapangus Press, 2024)
Infrastructure development, especially to improve facilities that support the realization of dreams for the future, also has an impact that is not easy in that problems will arise, in the form of land evictions which are called agrarian conflicts, agricultural conflicts arise as a result of incompatibility between two parties, and This agricultural conflict itself occurred in Sena Village. The aim of this research is to describe in depth the occurrence of evictions as a form of agrarian conflict in Sena Village. This research uses a qualitative research method using a case study approach. The data collection techniques used were documentation observation and interviews. The results of this research show that conflict occurs because local people claim that the land belongs to them, so they work on the land to build houses and also make land for farming as a source of their livelihood, due to the community's deep lack of understanding. Those on the land experienced eviction because the land they had been occupying had been state-owned land, thus resulting in positive and negative impacts from the eviction of the land. From these findings it can be concluded that as a society we must understand how to use land. If we do not understand the origin of the land, to whom it belongs, it will have a bad impact in the future, because state-owned land cannot be misused.